Effect of the Insertion and Polymerization Technique in Composite Resin Restorations: Analysis of Marginal Gap by Atomic Force Microscopy - Bomfim da Silva, Marcos Aurelio; Pimentel Lopes de Oliveira, Guilherme Jose [UNESP]; Tonholo, Josealdo; da Silva Junior, Jose Ginaldo; Santos, Lucineide de Melo; Limeira dos Reis, Jose Ivo (Cambridge University Press, 2010)
This in vitro study evaluated the marginal gap at the composite tooth/resin interface in class V cavities under the influence of two insertion techniques and a curing system by means of atomic force microscopy (AFM). Forty enamel and dentin cavities were prepared on the buccal surface in bovine teeth with quadratic forms measuring 2 mm X 2 mm and depth of 1.5 mm. The teeth were then divided into four groups: group A, 10 cavities were restored in one increment, light cured by halogen light; group B, 10 cavities filled with bulk filling, light cured by the light emitting diodes (LED); group C, 10 cavities were restored by the incremental technique, light cured by halogen light; group D, 10 cavities were restored by the incremental technique, light cured by the LED. The teeth underwent the polishing procedure and were analyzed by AFM for tooth/restoration interface evaluation. The data were compared between groups using the nonparametric Kruskall-Wallis and Mann-Whitney tests (p < 0.05). The results showed a statistically significant difference between groups A and B and groups A and C. It was concluded that no insertion and polymerization technique was able to completely seal the cavity.
Keywords: dental marginal adaptation; dental curing light; atomic force microscopy; composite resin; lasers; dental surface analysis